2020
DOI: 10.1038/s41386-020-00924-0
|View full text |Cite
|
Sign up to set email alerts
|

Convergent genomic and pharmacological evidence of PI3K/GSK3 signaling alterations in neurons from schizophrenia patients

Abstract: Human-induced pluripotent stem cells (hiPSCs) allow for the establishment of brain cellular models of psychiatric disorders that account for a patient’s genetic background. Here, we conducted an RNA-sequencing profiling study of hiPSC-derived cell lines from schizophrenia (SCZ) subjects, most of which are from a multiplex family, from the population isolate of the Central Valley of Costa Rica. hiPSCs, neural precursor cells, and cortical neurons derived from six healthy controls and seven SCZ subjects were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…Gene set enrichment analyses suggested involvement of pathways related to WNT signaling and forebrain development. Dysregulation of both of these pathways has been consistently observed in previous studies of SCZ using hiPSCs 16,[39][40][41] . In addition, we found that NPC DEGs correlated with neuronal DEGs, which is also consistent with previous findings 10 .…”
Section: Discussionsupporting
confidence: 66%
“…Gene set enrichment analyses suggested involvement of pathways related to WNT signaling and forebrain development. Dysregulation of both of these pathways has been consistently observed in previous studies of SCZ using hiPSCs 16,[39][40][41] . In addition, we found that NPC DEGs correlated with neuronal DEGs, which is also consistent with previous findings 10 .…”
Section: Discussionsupporting
confidence: 66%
“…While a growing body of research suggests that alterations in the AKT/GSK3 pathway activity is a common feature of many neuropsychiatric and neurodegenerative disorders ( Emamian et al, 2004 ; Emamian, 2012 ; Chen et al, 2015 ; McGuire et al, 2017 ; Stertz et al, 2020 ), studying the consequences of this purported dysfunction is difficult, considering the relatively quick activity of phosphatases post-mortem ( Li et al, 2005 ) and the paucity of available brains. In contrast, primary hippocampal neuronal cultures are an excellent in vitro model of basic neurobiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…AKT is activated through phosphorylation by PI3K, while GSK3 is a constitutively active kinase whose activity is decreased upon phosphorylation by AKT ( Sutherland et al, 1993 ; Jensen et al, 2007 ). Disruption of the AKT/GSK3 pathway has been shown to be a risk factor for neuropsychiatric and neurodegenerative disorders ( Crofton et al, 2017 ; Hsu et al, 2017 ; Scala et al, 2018 ; Stertz et al, 2020 ). Wee1 kinase is a complex enzyme that is regulated and degraded by GSK3 through ubiquitination ( Watanabe et al, 2004 ; Li et al, 2012 ; Penas et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gene expression profiles of five organs on days 1, 2, 4, 6, 8, and 14 after SARS-CoV-2 infection were compared with the normal control group (day 0) to identify the differences in gene expression in each organ, and all the differences in gene expression were combined to obtain the DEGs in each organ for further analysis. DEGs were screened using the DEseq2 function in R (version 3.6.3) ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%